Progress in Quantitative Adhesion Testing of Films and Coatings by means of Centrifuge Technology – Present State of the Art - Beck, Uwe; Hielscher, Stefan; Weise, Matthias; Mix, Renate; Lerche, Dietmar; Reitz, Uwe (International Conference on Plasma Surface Engineering, 2013)
Standardised conventional adhesion tests are time-consuming single-sample tests. Moreover, except for the pull-off test, all these tests provide only qualitative or semi-quantitative (ranking, respectively measurement of an adhesion-correlated quantity) information on adhesion. Sometimes, adhesion is evaluated even under compressive stress conditions (e.g. cross-cut and scratch test), which itself is a contradiction to adhesive strength as defined in terms of tensile force per area. For optical coatings it has been shown that the pull-off test in a centrifuge is definitely a promising alternative with respect to the reliable, fast and quantitative determination of adhesive strength in N/mm2. The force-controlled centrifuge test is the only multiple-sample test which provides reliable quantitative information on the adhesive strength in agreement with DIN EN 15870 and DIN EN ISO 4624 on a statistical basis for up to eight samples simultaneously tested under identical testing conditions.